Tuha Peut Perempuan: Peluang Dan Diferensiasi Sosial Pembangunan Gampong Di Aceh - Mahmuddin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
By marking Qanun no.5 2003 regarding “gampong/village governance and has been emphasized by UUPA no.11 2006 regarding Aceh Local Government is indicating new eras in “Social Identity of the Shadow Society” which had by forgotten during conflict eras in the region. The gampong governances that are consist of; Tuha Peut, geuchik and Teungku Imum which Tuha Peut is the consulting institution to support the Keuchiek were selected from the intellectual, schollars and youth and the women element personalities. The representativeness of women in Tuha Peut of the Gampong is turned to be a basic argument from the Act (No.5 year 2003) that previously had not been included in the structure of the gampong. The interference and the representativeness of women in the Gampong structural leader still considers as in the weak point. Women are not yet completely active in the Tuha Peut Leader institution structure of the gampong. Currently the culture of patriarchy that was noticed women as a second class citizen of the society and additionally the thought that is considering women as an inability actors in gampong development and being interfere in conflict solving of the Gampong is a basic problem in women reposition in gampong institutional structure.